2019
DOI: 10.1002/adfm.201900830
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimprinted Grating‐Embedded Perovskite Solar Cells with Improved Light Management

Abstract: Organic-inorganic halide perovskite solar cells are one of the most efficient photovoltaic devices, and their power conversion efficiency (PCE) continues to grow rapidly due to the optimization of device architecture and functional materials. The involved optical design has an important impact on performance by affecting the light harvesting capability. Here, demonstrated is a simple and effective strategy to boost device performance from the perspective of light management. A diffraction grating pattern into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 44 publications
0
70
0
Order By: Relevance
“…For the planar device, the absorption profile exhibits a laminar distribution because of the formation of standing wave. [ 35 ] For the NIO device, the absorption intensity is obviously higher than that of the planar device, and significant light absorption enhancement (red and dark red areas) is observed in the perovskite nanowall layer and the bulk area of the Spiro‐OMeTAD layer. The increased absorption intensity for the NIO device demonstrates improved light trapping effect resulting from the NIO structure.…”
Section: Figurementioning
confidence: 99%
“…For the planar device, the absorption profile exhibits a laminar distribution because of the formation of standing wave. [ 35 ] For the NIO device, the absorption intensity is obviously higher than that of the planar device, and significant light absorption enhancement (red and dark red areas) is observed in the perovskite nanowall layer and the bulk area of the Spiro‐OMeTAD layer. The increased absorption intensity for the NIO device demonstrates improved light trapping effect resulting from the NIO structure.…”
Section: Figurementioning
confidence: 99%
“…Unlike the above structures, some other interesting ordered array structures (grating and helices, and so on) are also employed to prepare ETL to improve device performance. 19,74,75,79 For example, Park et al fabricated helical TiO 2 arrays of different radius and pitch by an oblique-angle electron beam evaporation process ( Figure 5C). 74 Although the helical TiO 2 array had longer pathway compared to 1D vertical nanorod array, but it showed higher electron extraction efficiency due to the larger contact area between TiO 2 ETL and perovskite.…”
Section: D Ordered Array Structured Etlmentioning
confidence: 99%
“…(F) FDTD simulation of the PSCs based on flat TiO 2 and grating TiO 2 under different wavelengths incident light. Source: Reproduced from Reference 75 by permission from Wiley‐VCH…”
Section: Ordered Array Structures For Etlmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20] Jeong et al fabricated a variety of perovskite micropatterns, [21] Chun et al demonstrated a nanopillar photodetector with enhanced photoresponse [22] and a compact disc grating pattern was used to achieve more efficient and stable solar cells. [23,24] The process of SOMO is depicted in Figure 1a. Generally, the solution is deposited on the substrate to form a not yet crystallized, viscous thin film.…”
mentioning
confidence: 99%